Incidence and risk factors of delirium after percutaneous coronary intervention in individuals hospitalised for acute myocardial infarction: protocol for a systematic review and meta-analysis. Issue 12 (30th December 2020) - Huang, Kaizhuang; Lu, Jiaying; Zhu, Yaoli; Cheng, Tao; Du, Dahao; Qian, Xueqin; Pan, Haiyan; Wang, Xiaohua; Yang, Hong; Lou, Shaofei
Abstract : Introduction: Delirium in the postoperative period is a wide-reaching problem that affects important clinical outcomes. The incidence and risk factors of delirium in individuals with acute myocardial infarction (AMI) after primary percutaneous coronary intervention (PCI) has not been completely determined and no relevant systematic review and meta-analysis of incidence or risk factors exists. Hence, we aim to conduct a systematic review and meta-analysis to ascertain the incidence and risk factors of delirium among AMI patients undergoing PCI. Methods and analyses: We will undertake a comprehensive literature search among PubMed, EMBASE, Cochrane Library, PsycINFO, CINAHL and Google Scholar from their inception to the search date. Prospective cohort and cross-sectional studies that described the incidence or at least one risk factor of delirium will be eligible for inclusion. The primary outcome will be the incidence of postoperative delirium. The quality of included studies will be assessed using a risk of bias tool for prevalence studies and the Cochrane guidelines. Heterogeneity of the estimates across studies will be assessed. Incidence and risk factors associated with delirium will be extracted. Incidence data will be pooled. Each risk factor reported in the included studies will be recorded together with its statistical significance; narrative and meta-analytical approaches will be employed. The systematic review and meta-analysis will be presented according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Ethics and dissemination: This proposed systematic review and meta-analysis is based on published data, and thus there is no requirement for ethics approval. The study will provide an up to date and accurate incidence and risk factors of delirium after PCI among patients with AMI, which is necessary for future research in this area. The findings of this study will be disseminated through publication in a peer-reviewed journal. PROSPERO registration number: CRD42020184388.